Dengue and chikungunya viruses in plasma are effectively inactivated after treatment with methylene blue and visible light. Issue 9 (25th July 2016) - Fryk, Jesse J.; Marks, Denese C.; Hobson‐Peters, Jody; Prow, Natalie A.; Watterson, Daniel; Hall, Roy A.; Young, Paul R.; Reichenberg, Stefan; Sumian, Chryslain; Faddy, Helen M.
Abstract : BACKGROUND: Arboviruses, such as dengue viruses (DENV) and chikungunya virus (CHIKV), pose a risk to the safe transfusion of blood components, including plasma. Pathogen inactivation is an approach to manage this transfusion transmission risk, with a number of techniques being used worldwide for the treatment of plasma. In this study, the efficacy of the THERAFLEX MB‐Plasma system to inactivate all DENV serotypes (DENV‐1, DENV‐2, DENV‐3, DENV‐4) or CHIKV in plasma, using methylene blue and light illumination at 630 nm, was investigated. STUDY DESIGN AND METHODS: Pooled plasma units were spiked with DENV‐1, DENV‐2, DENV‐3 DENV‐4, or CHIKV and treated with the THERAFLEX MB‐Plasma system at four light illumination doses: 20, 40, 60, and 120 (standard dose) J/cm 2 . Pre‐ and posttreatment samples were collected and viral infectivity was determined. The reduction in viral infectivity was calculated for each dose. RESULTS: Treatment of plasma with the THERAFLEX MB‐Plasma system resulted in at least a 4.46‐log reduction in all DENV serotypes and CHIKV infectious virus. The residual infectivity for each was at the detection limit of the assay used at 60 J/cm 2, with dose dependency also observed. CONCLUSIONS: Our study demonstrated the THERAFLEX MB‐Plasma system can reduce the infectivity of all DENV serotypes and CHIKV spiked into plasma to the detection limit of the assay used at half of the standard illumination dose. This suggests this system has the capacity to be an effective option for managing the risk of DENV or CHIKV transfusion transmission in plasma.